Evaluasi dan Perancangan Ulang Tata Letak Gudang PT X dengan Metode Class Based Storage - Juliani, Kamilia Puteri; Herawaty, Tetty; Hakim, Raden Marsha Aulia (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2025)
This research aims to optimize the storage layout in the warehouse of PT X Bekasi Branch through the application of the class-based storage method with ABC analysis. Currently, the placement of stock is still done randomly which causes difficulties in finding goods, as well as long distances and travel times in retrieving goods. This study was conducted for three months from September to November with a qualitative descriptive method. The stages of the class-based storage method are determining the location based on the class where class A (fast moving) must be close to the entrance and exit access, class B (medium moving) does not have to be so close and class C (slow moving) can be very far. The results of this study show a reduction in distance and travel time with a total average distance of 1,361 cm, a percentage of 11.01% and a reduction in time of 20.01%. In addition, it also obtains a class division to determine the distance to the outbound access into 3 categories, namely the fast moving category of 22 items, medium moving of 11 items and slow moving of 11 items